Respostas
respondido por:
2
x² + 3x - 4 = 0
Δ = b²−4ac
Δ = (3)²−4⋅1⋅−4
Δ = 9+16
Δ = 25
x = -b ± √Δ / 2.a
x = -3 ± √25 / 2.1
x = -3 ± 5 / 2
x' = -3 + 5 / 2
x' = 2/2
x' = 1
x'' = -3 - 5 / 2
x'' = -8/2
x'' = -4
S ={1, -4}
Δ = b²−4ac
Δ = (3)²−4⋅1⋅−4
Δ = 9+16
Δ = 25
x = -b ± √Δ / 2.a
x = -3 ± √25 / 2.1
x = -3 ± 5 / 2
x' = -3 + 5 / 2
x' = 2/2
x' = 1
x'' = -3 - 5 / 2
x'' = -8/2
x'' = -4
S ={1, -4}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás